The Effect of Corporate Governance on Financial Performance and Tax Avoidance on LQ45 Companies - Rusni Syamsuddin; Muhammad Ali; Muhammad Sobarsyah (Hasanuddin Journal of Business Strategy, 2020)
Tax avoidance is a strategy applied by taxpayers to undertake legally burden taxes to decrease tax payment. Avoidance techniques by exploiting loopholes in tax laws. The purpose of this study is to examine the effect of corporate governance (institutional ownership, the board size, independent commissioners, audit boards) on tax avoidance (ETR) mediated by financial performance measured by Return on assets (ROA). The samples used were companies listed in the LQ45 index from the period of 2014 to 2018, with a total of 30 companies collected through purposive sampling. The study applied path analysis techniques using IBM SPSS 23 statistical software. These results indicate that corporate governance simultaneously influences financial performance and tax avoidance. Institutional ownership and audit committees have a positive and significant effect on financial performance. Interestingly, the size of the board of commissioners and independent commissioners were found insignificant to financial performance. To tax avoidance, the size of the board of commissioners, independent commissioners, and the audit board has a significant positive effect, but institutional ownership does not have a significant negative effect on tax avoidance, while financial performance negatively correlates to tax avoidance. Financial performance can mediate institutional ownership of tax avoidance. Differently, other independent variables did not show relationships.